Modelling the Diclofenac and Indomethacin Recovery by Molecularly Imprinted Polymer - Nurlin, Abu Samah; Sanchez-Martin, Maria-Jesus; Valiente, Manuel; López-Mesas, Montserrat (Penerbit Universiti Sains Malaysia, 2018)
Pharmaceutical compounds in surface waters are an emerging environmental concern due to their biological activity, which consequently present a new challenge for drinking water and wastewater treatment systems. In this work, diclofenac (DCF) and indomethacin (IDM) have been used as target molecules or templates in order to be removed by means of molecularly imprinted polymers (MIP). MIP-DCF and MIP-IDM were synthesised and tested using two mathematical models, which are Lagergren and Thomas models. In addition, functional groups of the active functional sites and the target molecules have also been studied by using Fourier transform infrared spectroscopy. Both MIPs followed the Lagergren pseudo first order kinetic model. Comparing the original MIP-DCF and MIP-DCF after loading with DCF, differences in their functional groups were found. In conclusion, MIP-DCF and MIP-IDM work as good sorbents to recover these emerging pharmaceuticals persistent pollutants from water.